CubeSat’s Deployable Solar Panel with Viscoelastic Multilayered Stiffener for Launch Vibration Attenuation - Shankar Bhattarai; Hongrae Kim; Hyun-Ung Oh (International Journal of Aerospace Engineering)
Ensuring the structural safety of a deployable solar panel under a severe launch vibration environment is one of the important factors for a successful CubeSat mission. A CubeSat’s deployable solar panel proposed in this study is effective to guarantee the structural safety of solar cells by attenuating launch loads owing to the superior damping characteristic achieved by a multilayered stiffener with viscoelastic acrylic tapes. The demonstration model of 3 U CubeSat’s deployable solar panel was fabricated and tested to validate the effectiveness of the proposed design. The basic dynamic characteristics of the solar panel were measured through free-vibration tests according to the various layers of the stiffener. Moreover, the characteristics of the deployed solar panel were measured and investigated under various temperatures to predict its capability under in-orbit operation. The effectiveness of the proposed design for launch vibration attenuation was demonstrated through qualification level sine and random vibration tests.